Urgent actions needed to prevent recurring food crises - Fan, Shenggen; Torero, Máximo; Headey, Derek D. (International Food Policy Research Institute, 2011)
Recent trends in food prices—higher levels and higher volatility—mirror trends predicted by a number of experts. Given the complex web of factors influencing global food security, governments of developed and developing countries, as well as international organizations, must use a comprehensive approach to prevent a food crisis reoccurrence. This comprehensive approach should comprise a number of initiatives and reforms; while some of these have been proposed before, their merits are even more relevant today and justify reprioritization and reallocation of national and international budgets. There are 7 main initiatives that governments and institutions should promptly implement. 1. Effective policies and technology investments to minimize food-fuel competition. 2. Social protection, especially social safety nets, for the most vulnerable groups. 3. Transparent, fair, and open global trade. 4. A global emergency physical grain reserve. 5. Policies and investments to promote agricultural growth, in particular smallholder productivity, in the face of climate change. 6. Investments by national governments in climate change adaptation and mitigation using the full potential that agriculture offers. 7. An international working group to regularly monitor the world food situation and trigger action to prevent excessive price volatility.